Ruang Komunal Toko Buku Dalam Novel Toko Buku Abadi Karya Yudhi Herwibowo Dan Book’s Kitchen Karya Kim Jee-Hye: Kajian Sastra Bandingan - Dian Hartati; Nabila Nurhidayah (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This research is motivated by differences in perspectives regarding the function and meaning of bookstores in the socio-cultural contexts of two countries. Bookstores are not only seen as places for buying and selling transactions, but also as social spaces that represent literacy culture and the dynamics of urban society. The purpose of this research is to identify the influences and similarities between two novels originating from different cultural backgrounds, while simultaneously exploring the communal space in books that is represented as a social and cultural space. This research examines the novels Toko Buku Abadi by Yudhi Herwibowo and the novel Book's Kitchen by Kim Jee Hye. The research focuses on two main aspects: first, revealing thematic similarities and writing styles that can indicate the existence of influence. Second, examining the function of bookstores in forming literacy communities. The results show that both novels display similarities in depicting bookstores as transitory spaces, momentary escapes, and places of nostalgia that reflect a longing for authentic literacy experiences. The bookstores in both works disguise the ideal function of a buying and selling space and the formation of a literacy community. From the perspective of intertextuality, no similarities or influences were found between the two novels. In each novel, the bookstore serves a social function as a communal space, reflecting challenges and cultural transformations. The representation of the bookstore in both works reflects the changing meaning of literacy spaces in urban society.